Diving Frequency Increase the Risk Barotrauma in Traditional Fisherman-Divers - Fatimah, Fatimah; Andarini, Sri; Astari, Asti Melani (Fakultas Kedokteran Universitas Brawijaya, 2019)
Barotrauma is a problem caused by differences between air pressures inside the body and in the environment. This condition causes damage to many organs and body tissues. Many factors influence the occurrence of barotrauma. However, the two factors that are not obviously influencing the incidence of barotrauma are the diving frequency and the diving resting time. This study aimed to identify the effect of diving frequency and resting time on barotrauma. This study used an observational analytic design through a case-control approach of 174 respondents. The results show p-value=0.000 and OR=5.48 that indicate an effect of diving frequency on barotrauma. The diving resting time does not influence barotrauma with p-value=0.621. The diving frequency is a factor that affects the incidence of barotrauma.